Investigation of antioxidant, antimicrobial, and enzymatic properties of thermophilic cyanobacteria extracts - Aytan Fataliyeva; Meral Yilmaz Cankilic; Nalan Yilmaz Sariozlu (BioTechnologia)
Background. The present study investigated the antioxidant, antimicrobial, and partial enzymatic properties of 52 thermophilic cyanobacteria isolates in vitro . Materials and methods. The DPPH scavenging method was applied to test the antioxidant potential of isolates’ methanol extracts. Agar block diffusion and agar well diffusion methods were used to evaluate the antimicrobial activity and measured in milimeters. The measurement of enzyme activity was carried out by a modification of the agar block method by the growth of the cyanobacteria. Results. Among the cyanobacterial extracts, strain 37 (0.78±0.055 mg/ml) showed an IC 50 value close to ascorbic acid (0.22±0.04 mg/ml), indicating that it has a specific antioxidant source. Isolate G13 was shown to have the strongest antimicrobial activity against Micrococcus luteus NRRL B-4375 in the agar well diffusion method. In addition, the ability to produce enzymes was determined in isolate G1 (25±5.66 mm), which had the highest cellulase activity at pH 8, and isolate K42 (22±0.71 mm), which had the highest lipase activity at pH 7. Conclusion. When percent inhibition and IC 50 values were examined, it was found that cyanobacterial methanol extracts had moderate and low scavenging activity in comparison to the standard antioxidant ascorbic acid. In a study using the agar well diffusion method, the activity of cyanobacterial extracts against test bacteria was observed. In light of the results obtained, it is believed that the isolates exhibited lipase and cellulase (pH 7 and 8) enzyme activity at both pH levels and have potential for industrial use.